Pulmonary Cystic Metastasis from Epithelioid Sarcoma Leading to Secondary Spontaneous Pneumothorax- A Case Report and Review of Literature - Singh, Priyanka; Vasan, Amit Singh; Ahuja, Nitin Balram; Singh, Sharanjit; Rana, Sandeep (Asian Pacific Journal of Cancer Care, 2025)
Well defined solid nodules are a recognized entity in pulmonary metastasis due to sarcoma, but cystic lung metastasis is seldom reported. A rare case of a 33 year old male presenting with left spontaneous pneumothorax secondary to underlying cystic metastasis from epithelioid sarcoma of left forearm is discussed. The Patient had undergone wide resection of epithelioid sarcoma in the left forearm 5 years back and had received chemotherapy for 2 years. His imaging study 2 years back did not reveal any evidence of metastasis. He presented to emergency department with acute onset left sided chest pain and breathlessness. A chest radiograph revealed spontaneous pneumothorax left side. A chest tube insertion and subsequent pleurodesis was done for the patient. He is on follow up and was restarted with chemotherapy. Oncologists need to be cognizant of this unusual sarcomatous metastasis and maintain high vigilance during the follow up of epithelioid sarcoma.